Simulation and Validation with Radio-Controlled (RC) Autonomous Vehicles in Roundabout Situation - Ferencz, Csanád; Zöldy, Máté (Periodica Polytechnica Transportation Engineering, 2022)
In the present research paper, the authors provide an extensive overview about a so far uninvestigated approach regarding the research and development (R&D) of Autonomous Vehicle Technologies, an exhaustive investigation concerning the simulation and validation of roundabout situation with radio-controlled (RC) autonomous vehicles, as well as the examination of RC vehicles’ applicability in the testing processes of Connected Autonomous Vehicle (CAV) technologies. Through this research project, the authors are offering a thorough analysis concerning the most current Autonomous Driving Systems from the point of view of their operation in roundabout related environments, as well as have developed two small-scaled RC autonomous vehicle models, which are capable of being used in the testing and validation processes concerning research studies related to the field of autonomous vehicles. This paper represents the first of a two-part in-depth examination of the aforementioned subject matter, organized in six sections, each contributing significantly to the realization of the final structure of a unique and comprehensive project.